Natural Hirudin Increases Rat Flap Viability by Anti-Inflammation via PARs/p38/NF-κB Pathway. (7th December 2015) - Peng, Liu; Pan, Xinyuan; Yin, Guoqian
Abstract : The present study aimed to evaluate the effect of natural hirudin on rat random skin flap viability and to determine the mechanism. Forty-eight rats were randomly divided into 2 groups. After the dorsal skin flap operation (3 cm × 10 cm in size), subcutaneous injections of 6 ATU hirudin were administered to group H (n = 24 ) every 12 h, while group C (n = 24 ) received an equal volume of 0.9% normal saline. Six rats from each group were euthanized 1, 2, 4, and 7 days after the operation. A full skin sample was collected from these rats to measure the p38-mitogen-activated protein kinase (p38-MAPK), phospho-p38- (Pp38-) MAPK, nuclear factor- κ B (NF- κ B) p65, phosphor-NF- κ B (pNF- κ B) p65, tumour necrosis factor- (TNF-) α, interleukin- (IL-) 6, and intercellular adhesion molecule- (ICAM-) 1 levels via western blot (WB) assays. The results showed that flap viability was significantly higher in the hirudin-treated group, which showed a reduced inflammatory response compared with the control group. The Pp38/p38, pNF- κ B p65/NF- κ B p65, TNF- α, IL-6, and ICAM-1 levels in the hirudin-treated group were lower than those in the control group. The results demonstrated that hirudin could improve random skin flap viability and suggested that this effect maybe occurs by blocking the thrombin/proteinase-activated receptors (PARs)/p38/NF- κ B signalling pathway, thus decreasing the inflammatory response.